Perencanaan Sistem Supply Chain Management untuk mengoptimalkan Rantai Pasok Bahan Baku Kopi di Tropic Pontianak - Agustinus Tantiono; Wendy (LPPM Universitas Widya Dharma Pontianak, 2025)
The phenomenon of working from a cafe, often known as Work From Cafe, has become increasingly popular since the rise of cafes or new places to enjoy coffee with unique concepts. Coffee has become the primary choice as a beverage that accompanies the work of employees and freelancers who implement work from cafes. With the increasing opportunity for coffee sales, coffee shops need to pay attention to supply management of the main raw material, namely coffee, in order to compete superiorly compared to competitors. The main objective of this study is to examine the importance of the supplier selection process, logistics planning, and distribution implemented by Tropic Pontianak. The activities of procuring raw materials until the final product reaches the hands of consumers are the main objectives of the study. The cafe business is one type of business that requires special attention to ensure consumer satisfaction with the consistency of the product served. Therefore, selecting the right raw materials and suppliers will be one way for cafe owners to survive in the era of fierce growth in the cafe business. Supply chain management is expected to show a vital role in increasing competitiveness and better operational management in order to compete closely with the growth of new cafe businesses.